Description of Comprehension, Perceptions, and Challenges of Science Teachers' Formative Assessment Practice in Wonosobo - Ismun Nisa Nadhifah; Agista Sintia Dewi Adila; Ayu Lestari (UNIB Press, 2023)
Many studies have demonstrated the effectiveness of formative science assessments, which were utilized in education in many industrialized nations as recently as two decades ago. The adoption of formative assessment procedures in Indonesia has, however, fallen short of expectations due to a number of factors, including the teachers' lack of understanding, preconceptions, and various challenges. Using an exploratory descriptive qualitative methodology, this study aimed to establish how teachers understand and perceive formative assessment, as well as the various implementation issues they experience in the classroom. Chi-square analysis was utilized to determine the correlations between the ordinal variables. The data were gathered through an online survey followed by interviews with five teachers possessing various profiles. It was determined that teachers' conceptual understanding and perceptions of formative assessment fell into the